High-toughness soft PBT (Polybutylene Terephthalate) face washing brush broken filament and preparation method thereof
By using modified PBT polymers, flexible segments and nanoparticle toughening agents in the face wash bristle filaments, the shortcomings of existing materials in softness and oxidation resistance are solved, and higher toughness, flexibility and oxidation resistance are achieved.
Patent Information
- Application Number
- CN202510083159.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-29
AI Technical Summary
The existing facial cleansing bristle silk materials have shortcomings in terms of flexibility and oxidation resistance, which are prone to breakage or fatigue damage during repeated use, and the antioxidant effect is not long-lasting.
Modified PBT polymer is used as the main component, and flexible segments and ethylene-vinyl acetate copolymer nanoparticles are added as toughening agents and antioxidants, so as to improve the dispersion of the toughening agent through ultrasonic dispersion technology.
It improves the balance between toughness and softness of the bristle silk, extends the service life, enhances the anti-oxidation and mechanical properties, and avoids the oxidation fading and mechanical properties of the material.
Smart Images

Figure CN119900103A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of toiletries, in particular to high-toughness and soft PBT face-washing brush bristles and a preparation method thereof. Background Art
[0002] At present, the common face-washing brush bristles on the market are mostly made of polyester or nylon materials. These materials have good strength and durability, but have certain deficiencies in softness and comfort, especially in the case of high requirements for skin mildness, such as face-washing brush bristles for facial skin. Many brush bristle materials in the prior art lack sufficient flexibility, especially in repeated bending and use, prone to breakage or fatigue damage, affecting the effect of long-term use. In addition, traditional face-washing brush bristles also perform poorly in terms of antioxidant properties, UV resistance and aging stability. As the use time increases, the color of the brush bristle will gradually fade, and even become brittle, resulting in its durability and service life being limited. This problem is mainly due to the material's own weak antioxidant capacity, especially in the case of long-term contact with water, air and ultraviolet rays, the material will gradually deteriorate, affecting its performance.
[0003] In the prior art, some high-performance facial brush bristle materials use toughening agents to improve their impact resistance and strength, but due to the poor dispersibility of the toughening agents, the toughening effect is often uneven, and even the material becomes fragile in some local areas. Specifically, some traditional toughening agents, such as common rubber toughening agents, have poor compatibility with the base material, and are prone to uneven dispersion of the toughening agents, which in turn leads to unstable overall performance of the bristle.
[0004] In addition, in the antioxidant design of facial brush bristle materials in the prior art, although some products will add antioxidants, they often fail to effectively optimize the characteristics of the material. Many antioxidant designs are too simple and lack targeted formulas, resulting in the antioxidant effect not being long-lasting and unable to meet the needs of high-intensity use environments. For products used for facial skin cleansing, antioxidant properties are particularly important, because during long-term use, the degradation of antioxidants directly affects the stability of the material and the overall life of the product. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides a high-toughness and soft PBT face-washing brush bristle and a preparation method thereof, which solves the problem that although toughening agents are used in existing materials to improve their impact resistance and strength, the toughening effect is often uneven due to the poor dispersibility of the toughening agents.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: a high-toughness and soft PBT facial brush bristle wire, the bristle wire is composed of a modified PBT polymer as a main component, the modified PBT polymer contains a flexible segment, the flexible segment is a polyether segment or a polyester segment, the mass percentage concentration of the modified PBT polymer is 60% to 80%, the bristle wire further contains a toughening agent, the toughening agent is ethylene-vinyl acetate copolymer nanoparticles, and the mass percentage of the toughening agent is 5% to 15%.
[0007] Preferably, the mass percentage of the flexible segment is 20% to 40%.
[0008] Preferably, the molecular weight of the modified PBT polymer ranges from 40,000 to 60,000 Da.
[0009] Preferably, the anti-oxidation property of the bristle filaments is obtained by compounding 1,4-butanediol and an antioxidant 1010, and the mass percentage of the antioxidant 1010 is 1% to 2%.
[0010] Preferably, the toughening agent is ethylene-vinyl acetate copolymer nanoparticles, the size of the EVA nanoparticles is 10 to 50 nanometers, and the particles are uniformly dispersed in the PBT polymer.
[0011] Preferably, the dispersibility of the toughening agent EVA nanoparticles is improved by ultrasonic dispersion technology to ensure uniform particle size and distribution.
[0012] The present invention also provides a method for preparing high-toughness and soft PBT face-washing brush bristles, comprising the following steps: Step 1: uniformly mixing the modified PBT polymer with a flexible segment, a toughening agent, a lubricant and an antioxidant, wherein the flexible segment is a polyether or polyester segment, the toughening agent is ethylene-vinyl acetate copolymer nanoparticles, the size of the toughening agent particles is 10 to 50 nanometers, and the particles are uniformly distributed; Step 2: feeding the uniformly mixed mixture into a screw extruder, performing melt extrusion in the extruder, and forming a filamentous product after extrusion; Step 3, cooling the extruded filament product through a cooling water tank to solidify it into shape; Step 4: The cooled filamentous product is pulled by a pulling device, and is dried and pressed, and finally rolled into a roll to obtain a high-toughness and soft PBT facial brush bristle.
[0013] Preferably, the mass percentage of the lubricant is 1% to 3%.
[0014] Preferably, the size of the toughening agent EVA nanoparticles is 10 to 50 nanometers, and the particles are evenly distributed by ultrasonic dispersion technology to ensure their dispersibility in the PBT polymer.
[0015] Preferably, the temperature of the cooling water tank is controlled between 30°C and 50°C.
[0016] The present invention provides a high-toughness and soft PBT face-washing brush bristle and a preparation method thereof. It has the following beneficial effects: 1. The present invention uses modified PBT polymer as the main raw material, combines with flexible segments such as polyether segments or polyester segments, and adds a toughening agent to the modified PBT polymer to achieve the technical effect of improving the toughness and softness of the material. Compared with the solution of using pure PBT or no toughening material in the prior art, the present invention effectively solves the problem that the bristles of the face washing brush are prone to brittleness and fracture while maintaining high strength, and achieves a better balance between toughness and softness, thereby improving the durability and comfort of the bristles of the face washing brush.
[0017] 2. The face-washing brush bristles of the present invention are added with antioxidant 1010 and optimized ratio, and after long-term oxidation aging test under high temperature and humidity, they show excellent antioxidant performance. Compared with the technical solutions in the prior art that use traditional antioxidant materials or lack antioxidant ingredients, the present invention effectively solves the problems of oxidation fading and mechanical property degradation of the bristles after long-term use, prolongs the service life and appearance retention of the face-washing brush bristles, and ensures its stability and reliability in long-term use.
[0018] 3. The present invention uses ethylene-vinyl acetate (EVA) copolymer nanoparticles as a toughening agent and optimizes its dispersibility through ultrasonic dispersion technology, which significantly improves the dispersion uniformity of the toughening agent in the PBT polymer. This technical solution effectively solves the local weakness of traditional toughening agents caused by uneven dispersion, enhances the overall mechanical properties and tensile strength of the bristle filaments, and makes the bristle filaments show higher impact resistance and durability in actual use.
[0019] 4. The present invention optimizes the material ratio by precisely controlling the ratio of modified PBT polymer to functional additives such as toughening agents and antioxidants, thereby achieving efficient material performance optimization effects. The optimized ratio scheme of the present invention effectively solves the problems of uneven performance and poor stability that are prone to occur in the material molding process, ensures the excellent performance of the facial brush bristles in different usage environments, and has better product consistency. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The present invention is a flow chart of the method. DETAILED DESCRIPTION
[0021] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] Please see attached Figure 1 An embodiment of the present invention provides a high-toughness and soft PBT facial brush bristle wire, wherein the bristle wire is mainly composed of a modified PBT polymer, wherein the modified PBT polymer contains a flexible segment, wherein the flexible segment is a polyether segment or a polyester segment, and the mass percentage concentration of the modified PBT polymer is 60% to 80%. The bristle wire further contains a toughening agent, wherein the toughening agent is ethylene-vinyl acetate copolymer nanoparticles, and the mass percentage of the toughening agent is 5% to 15%.
[0023] The mass percentage of the soft segments is 20% to 40%.
[0024] The molecular weight of the modified PBT polymer ranges from 40,000 to 60,000 Da.
[0025] The anti-oxidation property of the bristle is compounded by 1,4-butanediol and antioxidant 1010, and the mass percentage of antioxidant 1010 is 1% to 2%.
[0026] The toughening agent is ethylene-vinyl acetate copolymer nanoparticles, the size of the EVA nanoparticles is 10 to 50 nanometers, and the particles are uniformly dispersed in the PBT polymer.
[0027] The dispersibility of toughening agent EVA nanoparticles is improved by ultrasonic dispersion technology, ensuring uniform particle size and even distribution.
[0028] This embodiment also provides a method for preparing high-toughness and soft PBT face-washing brush bristles, comprising the following steps: Step 1, uniformly mixing the modified PBT polymer with a flexible segment, a toughening agent, a lubricant and an antioxidant, wherein the flexible segment is a polyether or polyester segment, the toughening agent is ethylene-vinyl acetate copolymer nanoparticles, the size of the toughening agent particles is 10 to 50 nanometers, and the particles are uniformly distributed; Step 2: feeding the uniformly mixed mixture into a screw extruder, performing melt extrusion in the extruder, and forming a filamentous product after extrusion; Step 3, cooling the extruded filament product through a cooling water tank to solidify it into shape; Step 4: The cooled filamentous product is pulled by a pulling device, and is dried and pressed, and finally rolled into a roll to obtain a high-toughness and soft PBT facial brush bristle.
[0029] The mass percentage concentration of the modified PBT polymer is 60% to 80%, the mass percentage of the flexible segment is 20% to 40%, the mass percentage of the toughening agent is 5% to 15%, the mass percentage of the lubricant is 1% to 3%, and the mass percentage of the antioxidant is 1% to 2%.
[0030] The size of the toughening agent EVA nanoparticles is 10 to 50 nanometers, and the distribution of the particles is uniformly distributed through ultrasonic dispersion technology to ensure its dispersibility in the PBT polymer.
[0031] The temperature of the cooling water tank is controlled between 30℃ and 50℃.
[0032] In this embodiment, the first step is to mix the components in a predetermined ratio to ensure that the obtained high-toughness and soft PBT facial brush bristles have the expected physical and mechanical properties. This step is the basis of the entire preparation process. By uniformly mixing the modified PBT polymer, the flexible segment, the toughening agent, the lubricant, the antioxidant and other functional additives, the uniform distribution of each component in the final product is ensured, so as to obtain the ideal product effect in the subsequent extrusion and molding process.
[0033] In this step, the proportion, mixing method and mixing uniformity of each component directly affect the flexibility, wear resistance, oxidation resistance and other physical properties of the final bristle filament. Therefore, precise proportioning and uniform mixing are the key to ensuring quality stability.
[0034] Specifically, in this embodiment, the components are mixed in the following proportions: Modified PBT polymer: 60% to 80% Flexible segments: 20% to 40% Toughener (ethylene-vinyl acetate copolymer nanoparticles, EVA): 5% to 15% Lubricant: 1% to 3% Antioxidants (e.g. 1,4-butanediol mixed with antioxidant 1010): 1% to 2% The modified PBT polymer is used as the main base material, and its mass percentage is controlled at 60% to 80%. The flexibility is improved mainly by introducing flexible segments to enhance the durability and comfort of the product. Specifically, the mass percentage of the flexible segments is 20% to 40%, and these segments can be polyether segments or polyester segments. The addition of flexible segments can break the rigid structure of the PBT polymer, making the final bristle filaments have higher flexibility and fracture resistance, which is especially suitable for occasions such as facial cleaning where the softness of the bristles is required.
[0035] The mass percentage of the toughening agent is 5% to 15%, and ethylene-vinyl acetate copolymer (EVA) nanoparticles are selected as the toughening agent. Specifically, the size of the EVA nanoparticles is controlled between 10 and 50 nanometers. The nanoparticles have a large specific surface area and can provide excellent reinforcement in the polymer matrix, increase the toughness of the material and prevent fracture. In order to ensure the uniform distribution of the toughening agent, it can be processed by ultrasonic dispersion technology to ensure good dispersibility and uniform distribution of the particles.
[0036] The mass percentages of lubricants and antioxidants are 1% to 3% and 1% to 2%, respectively. The main function of lubricants is to improve fluidity during processing, reduce friction during extrusion, prevent excessive wear of materials and ensure smooth processing. Common lubricants include zinc stearate, which can effectively reduce friction without affecting the final performance. The compounding of antioxidant 1010 and 1,4-butanediol is mainly used to improve the antioxidant capacity of the material, prevent oxidation problems of the material during processing, and ensure the long-term stability of the bristle filaments.
[0037] In some embodiments, other functional additives, such as flame retardants, ultraviolet absorbers, etc., may be added as needed to further enhance the additional functions of the product.
[0038] In this embodiment, the raw materials can be mixed uniformly by mechanical stirring, electrostatic mixing, solvent method or heat treatment, and the specific method can be selected according to the equipment used and the required performance. Mechanical stirring is the most common method, and a high shear agitator is usually used for mixing to ensure that the components are completely fused without stratification or uneven dispersion. The stirring time is usually 10 to 30 minutes to ensure that all components can be fully mixed and reach a uniform state.
[0039] In actual operation, the order and method of adding the soft segments, toughening agents and lubricants will also affect the mixing effect. Usually, the modified PBT polymer is the first substrate to be added, followed by the gradual addition of the soft segments, toughening agents, lubricants and antioxidants. When adding the toughening agent, it can be pre-mixed with the lubricant first, which helps to avoid the agglomeration of the toughening agent particles and ensures its uniform dispersion in the PBT matrix.
[0040] In some embodiments, the particle size of the toughening agent EVA can be further adjusted according to the desired performance. In some cases, EVA nanoparticles with smaller particle size can provide better reinforcement, but may also result in poor dispersibility, so it needs to be optimized according to different product requirements.
[0041] In addition, when batching and mixing, the continuity and automation of production also need to be considered. In large-scale production, an automated batching system is usually used, which can accurately control the ratio of each component to ensure the stability and consistency of each production.
[0042] In general, this embodiment can obtain PBT facial brush bristles with good flexibility, durability and antioxidant properties by accurately proportioning the components and adopting an appropriate mixing method. The superiority of this mixing process lays a solid foundation for the subsequent extrusion molding step and ensures the quality stability and performance reliability of the final product.
[0043] In this embodiment, step 2 is one of the key steps in the entire preparation process, and the uniformly mixed raw materials are transformed into the desired filamentary form by melt extrusion. Melt extrusion technology is an efficient plastic processing method that can ensure uniform heating, melting and continuous extrusion of raw materials, thereby ensuring the consistency of the performance and morphology of the final bristle filaments.
[0044] In the above step 1, the modified PBT polymer, soft chain segment, toughening agent, lubricant and antioxidant components have been mixed in a predetermined ratio to ensure the uniform distribution of each component in the raw material. After the mixing is completed, the resulting material will be sent to the screw extruder for further processing. The screw extruder is a device that propels the material through the rotation of the screw. It can efficiently mix and melt the material during the heating process and extrude the material into a specific shape through the mold.
[0045] In this embodiment, the temperature control of the screw extruder is crucial to the preparation process. Generally, the temperature setting of the extruder needs to be adjusted according to the melting point range of different materials. Specifically, during the melting process of the polybutylene terephthalate (PBT) matrix, the temperature is usually set between 230°C and 270°C. Due to the addition of flexible segments and toughening agents, the required temperature range can be slightly adjusted to ensure good fluidity and processability of the material.
[0046] Specifically, the temperature distribution of the extruder is usually divided into three stages: feeding section, melting section and metering section. The temperature of the feeding section is relatively low, about 150℃ to 180℃, which is used to gradually heat and soften the material; the temperature of the melting section is relatively high, about 230℃ to 270℃, to ensure that the material is completely melted; the temperature of the metering section is slightly lower, usually set at 200℃ to 220℃, to ensure that the molten material can flow smoothly through the mold and form.
[0047] In some embodiments, in order to ensure the uniformity and fluidity of the PBT material, the screw speed of the screw extruder can be set within the range of 50-100 rpm. The screw is usually designed as a multi-stage screw with different spiral angles and different compression sections to ensure that the material is fully mixed and plasticized during the extrusion process. In this process, the friction between the screw and the barrel will heat the raw material to its melting temperature, and under the action of the spiral rotation, the raw material material will be in a uniform molten state.
[0048] It should be noted that in this embodiment, strict requirements are placed on the dispersibility of the toughening agent (such as EVA nanoparticles) during the melt extrusion process. The uniform distribution of the toughening agent has an important influence on the mechanical properties of the final bristle filaments. If the toughening agent is not evenly dispersed, it may lead to unstable performance in local areas, thereby affecting the flexibility and fracture resistance of the bristle filaments. To this end, the screw speed, temperature distribution and pressure are precisely controlled so that the toughening agent can be evenly distributed throughout the PBT polymer matrix. In some embodiments, the dispersibility of the toughening agent can be further improved by selecting a suitable screw structure and optimizing process parameters.
[0049] In practice, in order to optimize the performance of this step, it may be necessary to adjust the screw design and temperature control according to different raw material ratios or target product requirements. For example, in some cases, the design of the screw extruder may adopt a twin-screw structure instead of a single-screw structure. Twin-screw extruders have better mixing performance and can heat and mix materials evenly in a shorter time, thereby improving production efficiency and product consistency.
[0050] Furthermore, the process parameters of melt extrusion have an important influence on the quality of the final bristle filament. In some embodiments, the adjustment of parameters such as material flow rate, stretching speed and temperature gradient after extrusion can optimize the physical properties of the bristle filament. For example, a higher extrusion temperature can improve the fluidity of the material and ensure smooth flow in the mold, while a lower extrusion temperature helps control the solidification speed of the material and avoid molding defects caused by too high or too low temperature.
[0051] In some embodiments, in order to improve production efficiency, multiple extruders may be used in parallel to form a multi-channel molten material processing system. This method can not only increase production, but also adjust the parameter settings of each production line according to different raw material ratios, thereby achieving more efficient production.
[0052] In this embodiment, the design of the mold used in the screw extrusion process is also an important factor affecting the quality of the final bristle filaments. To ensure the slender shape of the bristle filaments, the design of the mold should have a reasonable discharge port and temperature control system to prevent the material from being blocked or unevenly formed when passing through the mold. The shape of the discharge port of the mold is usually circular or rectangular, and the appropriate size and shape can be selected according to actual needs.
[0053] In summary, the melt extrusion process in step 2 mainly ensures that the modified PBT polymer and its additives can be smoothly melted and extruded by precisely controlling the temperature, screw speed and pressure. At the same time, the uniform distribution of the toughening agent and the full plasticization of the material are key factors to ensure the quality and performance of the final bristle. By optimizing these process parameters, high-toughness and soft PBT facial brush bristles with excellent performance can be produced to meet the high requirements of personal care products for material softness, durability and comfort.
[0054] In this embodiment, step three is a crucial part of the preparation process of high-toughness and soft PBT face brush bristles. The extruded filament product is cooled by a cooling water tank, so that the hot-melt PBT bristle filaments are solidified and formed into the desired physical form. The cooling process not only helps the solidification and molding of the material, but also has an important impact on the microstructure, surface quality and final performance of the product.
[0055] In the above step 2, the PBT raw material melt-extruded by the screw extruder has been converted into a molten material with a certain fluidity, and extruded into a filament through a die. The temperature of the filament needs to be gradually lowered during the cooling process to ensure that its structure is stable and has no deformation. The cooling molding step can effectively avoid dimensional instability or internal stress accumulation caused by uneven cooling while ensuring that the material is well formed.
[0056] In this embodiment, the cooling process is mainly completed by a cooling water tank. The cooling water tank uses a circulating cooling water flow to accelerate cooling, ensure that the material maintains a uniform temperature distribution during the cooling process, and quickly cools the surface of the material to avoid excessive solidification of the outside and the formation of uneven stress differences inside and outside. Generally, the water temperature of the cooling water tank is usually controlled between 20°C and 30°C. Through full contact with the cooling water tank, the extruded PBT filaments will gradually change from a molten state to a solid state, completing the transformation from a flowing state to a solid state.
[0057] In order to improve the cooling effect, the design of the cooling water tank usually needs to consider factors such as its length, width and water flow rate. Specifically, the length and width of the cooling water tank should match the linear speed of the extruded filament to ensure that the material can be cooled evenly during the cooling process. Generally, the water flow rate is between 2-4m / s, which can effectively improve the cooling efficiency and avoid uneven cooling caused by too slow or too fast water flow.
[0058] In addition, in some embodiments, in order to improve cooling efficiency and uniformity, the water flow of the cooling water tank may adopt a flow optimization design, such as a bellows or spiral flow channel design, so that the cooling water flow can contact the extruded bristle filaments more evenly, further improving the cooling effect. In particular, multiple water pumps and water pipe systems can be set inside the cooling water tank to achieve uniform distribution of water flow, avoiding overheating or overcooling in local areas.
[0059] During the cooling process, if there is a large tension or internal stress, the shape of the PBT bristle filament may become unstable or produce microcracks. Therefore, in some embodiments, a certain pre-stretching section is set between the cooling water tank and the traction device. This design not only helps to avoid stress problems during the cooling process, but also controls the outer diameter and roundness of the bristle filament during the cooling process, ensuring that the final product has a good shape and stability.
[0060] In some embodiments, in addition to controlling the temperature and water flow rate in the cooling water tank, other cooling means may be combined, such as an air cooling device or a cooling tower, to further improve the cooling effect and production efficiency. For example, after cooling in the water tank, after a certain length of cooling section, the temperature of the filaments can be further reduced to room temperature through an air circulation device to prepare for the subsequent drawing and drying steps.
[0061] Specifically, during the cooling process, the surface temperature of the PBT bristle filament will quickly drop to below 6°C, while the temperature of the inner layer will drop to a solidified state slightly later than the surface. During the cooling process, the uniformity of the temperature drop is crucial to the quality of the final molded product. In some embodiments, the control of the cooling rate can further optimize the mechanical properties of the bristle filament, for example, by adjusting the cooling water flow rate or cooling time, controlling the temperature difference between the inner and outer layers of the bristle filament, so that it has better wear resistance and flexibility.
[0062] It should be noted that there are many technical points in the cooling process, including cooling uniformity, cooling rate, cooling water temperature control, etc., all of which may have a significant impact on the physical properties and performance of the final product. In some embodiments, precise control of cooling temperature is one of the important measures to ensure the quality consistency of bristle filaments. After the cooling section, after a certain cooling process, the bristle filaments will be completely solidified in the cooling water tank, and then enter the next step of traction and drying.
[0063] In this embodiment, the design of the cooling molding process not only improves production efficiency, but also effectively ensures the physical properties and morphological stability of the bristle filaments. By reasonably controlling the flow rate of the cooling water flow, the length of the cooling water tank, the cooling time and other parameters, the final product can be fully optimized in terms of flexibility, tensile strength and fracture resistance, providing a good foundation for subsequent drying, pressing and winding steps.
[0064] In this embodiment, step 4 is an important step in the preparation process of high-toughness and soft PBT face-washing brush bristles, which aims to achieve the final physical form and surface quality requirements of the cooled and formed PBT bristle filaments through traction, drying and pressing. This step not only helps to ensure the dimensional stability and morphological consistency of the bristle filaments, but also optimizes their mechanical properties and surface finish, laying the foundation for the quality of the final product.
[0065] In the aforementioned step three, the PBT bristle filaments have completed preliminary cooling and solidification through the cooling water tank. However, the cooled filaments are still in a relatively soft state, and there may be a certain amount of moisture or surface unevenness on the surface. Therefore, the process of traction, drying and pressing is of great significance for improving the quality of the bristle filaments. Through precise control of traction, drying and pressing, the internal stress that may exist in the cooling process can be effectively eliminated, shape distortion or surface defects can be avoided, and the surface smoothness and gloss of the bristle filaments can be improved.
[0066] In this embodiment, the cooled PBT bristle wire is firstly pulled by a pulling device. The main purpose of the pulling is to further stretch and shape the bristle wire that has been cooled and formed, so that it maintains a certain straightness and outer diameter. In general, the pulling device should have a precise line speed control system to ensure that the stretching process of the bristle wire is uniform and stable. In some embodiments, the pulling device adopts a servo motor driven traction system, which can achieve fine adjustment of the stretching speed and ensure that the bristle wire is uniformly stressed during the traction process.
[0067] During the pulling process, the drawing speed of the bristle wire usually needs to be adjusted according to the raw material characteristics and cooling state of the bristle wire. Specifically, the setting of the pulling speed needs to consider the flexibility and tensile strength of the bristle wire to avoid over-stretching or under-stretching. The pulling speed range is generally controlled between 10-50m / min, and the specific pulling speed can be optimized and adjusted according to actual production needs.
[0068] Afterwards, the bristle filaments after traction enter the drying stage. The main purpose of drying is to remove moisture from the surface of the bristle filaments and further stabilize the physical properties of the bristle filaments. In this process, hot air drying is usually used. The temperature and wind speed of the hot air drying system need to be precisely set according to the material characteristics of the bristle filaments and the production process requirements. Generally, the drying temperature is controlled between 60°C and 100°C, and the drying wind speed is 1-2m / s to ensure that the drying process is uniform and does not affect the mechanical properties of the bristle filaments.
[0069] In some embodiments, the drying system may also be equipped with a temperature and humidity sensor to monitor the temperature and humidity changes of the drying environment in real time, thereby further improving the accuracy and consistency of the drying process. In particular, during the production process, if the moisture on the surface of the bristle filaments is not completely removed, it may cause deformation or unsatisfactory surface gloss during the subsequent pressing process. Therefore, precise control of the drying step is the key to ensuring the quality of the final product.
[0070] After drying, the bristle filaments will enter the pressing stage. Pressing is the process of flattening the pulled and dried bristle filaments. Its purpose is to ensure a smooth surface of the bristle filaments and avoid defects caused by uneven surfaces that affect the aesthetics and practical application performance of the bristle filaments. Pressing equipment usually uses heated rollers or calendering equipment for processing. By accurately controlling the pressing pressure and roller temperature, the surface unevenness can be effectively removed and the surface finish of the bristle filaments can be improved.
[0071] The pressure and temperature control during the lamination process are crucial to the final surface effect of the product. Generally, the lamination pressure ranges from 0.2-0.5MPa, and the temperature is controlled between 80℃ and 120℃. The specific temperature and pressure parameters can be fine-tuned according to production requirements. In some embodiments, the lamination equipment may also be equipped with a smooth roller to further improve the surface finish of the bristle filament.
[0072] It should be noted that excessive pressure during the lamination process will lead to excessive compression of the bristle filaments, affecting their softness; while too little pressure may cause an uneven surface, affecting the appearance of the final product. Therefore, precise control of the lamination pressure is very critical. At the same time, the surface roughness of the roller and the adjustment of the roller gap will also have a direct impact on the surface quality of the bristle filaments. In some embodiments, in order to further improve the surface effect, the smoothing effect of the lamination process can be improved by chrome-plating the roller surface or using special coating technology.
[0073] In summary, through the steps of traction, drying and pressing, this embodiment can effectively ensure the morphological stability, surface smoothness and final mechanical properties of the high-toughness and soft PBT face-washing brush bristles, ensuring that the bristles have excellent softness, durability and tensile resistance in subsequent use. These treatments not only improve the physical properties of the bristle filaments, but also improve their appearance quality, providing a better product experience for the final consumer.
[0074] Embodiment 1: Mixed raw materials: Modified PBT polymer (mass percentage: 75%), flexible segment (polyether segment, mass percentage: 25%), ethylene-vinyl acetate copolymer nanoparticles (toughener, mass percentage: 10%), 1% antioxidant (antioxidant 1010) and lubricant (1%) were selected. All raw materials were uniformly mixed in a high-speed stirrer according to a predetermined ratio.
[0075] During the mixing process, ultrasonic technology was used to ensure uniform dispersion of ethylene-vinyl acetate copolymer nanoparticles, with the particle size maintained at around 30 nanometers.
[0076] Melt extrusion: The mixed materials were fed into a twin-screw extruder, the temperature was set in the range of 210-250°C, and the screw speed was set at 120 rpm.
[0077] The material obtained after extrusion is cooled to form a preliminary PBT filament product.
[0078] Traction, drying and pressing: The pulling speed is controlled at 20m / min to ensure the straightness and outer diameter stability of the bristle wire.
[0079] Use hot air drying equipment for drying, control the drying temperature to 90°C, the wind speed to 1.5m / s, and the duration to 5 minutes to ensure that the surface moisture is completely removed.
[0080] The pressing is performed by heated rollers, the pressing temperature is set at 100°C, and the pressure is controlled at 0.3MPa to ensure that the surface of the bristle filaments is smooth and the shape is uniform.
[0081] Embodiment 2: Mixed raw materials: Modified PBT polymer (mass percentage: 70%), polyester flexible chain segment (mass percentage: 30%), ethylene-vinyl acetate copolymer nanoparticles (mass percentage: 8%) and functional additives such as antioxidant (1.5%), lubricant (1.5%) and whitening agent.
[0082] By using solution mixing technology, the uniform dissolution of the polyester chain segments is ensured, and appropriate amounts of antioxidants and lubricants are added.
[0083] Melt extrusion: A twin-screw extruder was used with a set temperature of 230-270°C and a screw speed of 100 rpm to ensure that the modified PBT polymer and toughening agent were fully melted and uniformly mixed.
[0084] Traction, drying and pressing: The pulling speed is controlled at 25m / min to ensure the consistency of the outer diameter and smooth surface of the bristle wire.
[0085] Use hot air drying equipment, the temperature is controlled at 95℃, the wind speed is 1.2m / s, and the drying time is 7 minutes.
[0086] During pressing, the temperature was set to 110°C, the pressure was set to 0.4 MPa, and the pressing time was set to 1 minute.
[0087] Embodiment three: Mixed raw materials: Modified PBT polymer (mass percentage: 80%), polyether flexible segment (mass percentage: 20%), ethylene-vinyl acetate copolymer nanoparticles (toughener, mass percentage: 12%), and bio-based antioxidants and environmentally friendly lubricants (mass percentage: 2%) are used.
[0088] All raw materials are recyclable, and the selected toughening agents are environmentally friendly materials that meet sustainable development standards.
[0089] Melt extrusion: In the twin-screw extruder, the temperature is set at 220-240°C and the screw speed is 110rpm to ensure that the materials can be fully mixed while maintaining environmental protection and avoiding degradation of the materials due to excessively high temperatures.
[0090] Traction, drying and pressing: The pulling speed was 15 m / min, the drying temperature was controlled at 80°C, the wind speed was 1.0 m / s, and the drying time was 6 minutes.
[0091] In the pressing process, the temperature was set to 95°C, the pressure was set to 0.35 MPa, and the pressing time was set to 0.8 minutes.
[0092] Embodiment 4: Mixed raw materials: Modified PBT polymer (mass percentage: 78%), flexible segments (polyether segments, mass percentage: 22%), ethylene-vinyl acetate copolymer nanoparticles (toughener, mass percentage: 7%) and surfactant (0.5%) improve the surface finish of the final product.
[0093] The toughening agent adopts ultra-fine nanoparticles to ensure its uniform dispersion in the mixture.
[0094] Melt extrusion: The mixture was fed into a twin-screw extruder with a set temperature of 240°C and a screw speed of 120 rpm. This temperature condition can effectively prevent particles from agglomerating at high temperatures and ensure uniform mixing.
[0095] Traction, drying and pressing: The pulling speed is controlled at 20m / min to ensure that the outer diameter of the bristle filament is stable and the shape is uniform.
[0096] The drying temperature was set at 85 °C, the wind speed was 1.3 m / s, and the drying time was 5 min to remove moisture and improve the finish.
[0097] During the pressing process, the temperature was set at 100°C and the pressure was controlled at 0.4MPa to further improve the surface smoothness and appearance quality of the bristle filaments.
[0098] Comparative Example 1: Contrasting Designs: Material composition: Comparative Example 1 uses traditional PBT polymer as the main component of the bristle filaments, but does not add flexible segments and toughening agents.
[0099] Toughening agent: Ethylene-vinyl acetate copolymer (EVA) nanoparticles were not used as toughening agent, but only ordinary non-toughening materials were used.
[0100] Process steps: Mixed raw materials: In Comparative Example 1, only PBT polymer and a small amount of antioxidant (antioxidant 1010) were used, and no soft segment and toughening agent were added.
[0101] Melt extrusion: The mixed materials were fed into a twin-screw extruder for melt extrusion at a temperature of 240 °C and a screw speed of 100 rpm.
[0102] Drawing, drying and pressing: The extruded filament product is drawn at a speed of 20 m / min and undergoes conventional drying and pressing treatments.
[0103] Comparative Example 2: Contrasting Designs: Material composition: In comparative example 2, modified PBT polymer (mass percentage 70%) is used, and ordinary EVA particles are added as a toughening agent. Different from the EVA nanoparticles of the present invention, EVA particles with large particle size (more than 100 nanometers) are used in the comparative example.
[0104] Toughening agent: ordinary EVA particles were used instead of nanoparticles.
[0105] Process steps: Mixed raw materials: Modified PBT and ordinary EVA particles are mixed in a ratio of 70%:10%, and 1% antioxidant (antioxidant 1010) and lubricant are added.
[0106] Melt extrusion: The mixed materials are fed into a twin-screw extruder for melt extrusion at a temperature of 250°C and a screw speed of 120 rpm. Due to the large particle size of EVA particles, the fluidity of the material is poor during the extrusion process, and the molding effect is relatively poor.
[0107] Traction, drying and pressing: The extruded material is subjected to conventional traction and pressing treatment, with a traction rate of 20 m / min and a pressing temperature of 90°C.
[0108] Comparative Example 3: Contrasting Designs: Material composition: Comparative Example 3 uses the same modified PBT polymer and flexible segment (polyether segment) as the present invention, but reduces the extrusion temperature and screw speed to 210°C and 80rpm in the process to save energy.
[0109] Process steps: Mixed raw materials: According to the method of the present invention, modified PBT and flexible segments are used in the same proportion, and antioxidants and lubricants are added.
[0110] Melt extrusion: Extrusion was carried out at a relatively low temperature (210°C) and a relatively low screw speed (80 rpm).
[0111] Traction, drying and pressing: The pulling rate and drying process of the extruded product are the same as those in Example 1. However, due to the lower extrusion temperature, the product is not completely melted and has a certain roughness on the surface.
[0112] Comparative Example 4: Contrasting Designs: Material composition: Comparative Example 4 uses the same material composition as Example 1 (modified PBT polymer, flexible chain segment, toughening agent EVA nanoparticles), but no antioxidant is added.
[0113] Process steps: Mixed raw materials: the same raw material ratio as in Example 1, but without adding antioxidant.
[0114] Melt extrusion: melt extrusion was carried out according to the process parameters of Example 1, with a temperature of 240° C. and a screw speed of 110 rpm.
[0115] Drawing, drying and pressing: the drawing, drying and pressing conditions of Example 1 were followed.
[0116] Experiment 1: Flexibility test Experimental Description The purpose of this experiment is to evaluate the flexibility of different materials through a three-point bending test, focusing on comparing the differences in flexibility between the examples of the present invention and the comparative examples. Specifically, Example 1 improves the flexibility of the PBT material by adding a flexible segment (polyether segment or polyester segment) and a toughening agent (EVA nanoparticles), while the comparative example group fine-tunes different parameters to verify the synergistic effect of the flexible segment and the toughening agent on the material properties.
[0117] Experimental steps: Sample preparation: According to the formula of different groups, mix and prepare the bristle samples in the following proportions: Example 1: A modified PBT polymer is used, comprising a flexible segment (polyether segment or polyester segment) and a toughening agent (EVA nanoparticles), and the toughening agent content is 10%.
[0118] Comparative Example 1: Using traditional PBT polymer without adding flexible segments and toughening agents.
[0119] Comparative Example 2: A soft segment (polyether segment or polyester segment) was added, but no toughening agent was used.
[0120] The above ingredients were extruded into bristle filaments by melt extrusion and cut into samples with a length of about 50 mm.
[0121] Three-point bending test: Each sample was placed on a three-point bending test apparatus with a support frame spacing of 50 mm.
[0122] A gradually increasing force is applied and the flexural modulus and the strain at break of the sample are recorded.
[0123] During the test, the bending speed was 1 mm / min until the sample bent or broke.
[0124] Each group of samples was tested at least 5 times and the average value was taken.
[0125] Data recording: record key data such as maximum bending stress, fracture strain, bending modulus, etc. of each sample.
[0126] Data analysis: Compare the test results of different groups and evaluate the effect of toughening agents and flexible segments on improving material flexibility. Sample No. Flexural modulus Fracture strain Maximum bending stress Embodiment 1 1500MPa 8.2% 15.4MPa Comparative Example 1 2000MPa 4.5% 10.7MPa Comparative Example 2 1700MPa 6.1% 12.2MPa Comparative Example 3 2100MPa 5.0% 11.0MPa
[0127] Table 1 It can be seen from the experimental data that the bristle filaments of Example 1 are superior to the comparative example group in terms of bending modulus, fracture strain and maximum bending stress. This shows that the synergistic effect of the toughening agent (EVA nanoparticles) and the flexible segment has a significant improvement effect on the flexibility of the PBT material. Specifically, the addition of EVA nanoparticles effectively increases the plasticity of the material, by increasing the slippage of the molecular chain and reducing the rigidity of the material, so that the material can better absorb stress when bending and avoid brittle fracture. The flexible segment (polyether segment or polyester segment) further improves the flexibility and toughness of the material by reducing the interaction between the molecular chains.
[0128] For Comparative Example 1, due to the lack of toughening agent and flexible segments, the PBT material is prone to brittle fracture when subjected to external force, so its bending modulus and fracture strain are both low. Although the flexible segments are added to Comparative Example 2, the effect of toughening agent is lacking, resulting in the effect of improving its flexibility not being as good as that of Example 1. Although the flexible segments are added to Comparative Example 3, the particle size of the toughening agent particles is large (nanoparticles are not used), so a uniform toughening effect cannot be formed in the material, resulting in poor flexibility.
[0129] Through the above analysis, it can be confirmed that the combination of the nanoparticle form of the toughening agent and the flexible segment plays an important role in the present invention, which improves the flexibility of the material while avoiding the brittle fracture of the material.
[0130] Experiment 2: Material Antioxidation Performance and Thermal Stability Test Purpose This experiment aims to compare the antioxidant performance and thermal stability of different examples and comparative examples, test the stability of each sample under high temperature environment, and the role of its antioxidant (such as antioxidant 1010) in improving material performance. The effect of toughening agent, flexible chain segment and antioxidant on the performance of PBT facial brush bristles is analyzed by thermal gravimetric analysis (TGA) and oxidation index test (OIT).
[0131] Experimental Materials Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3 (the samples described above) Antioxidant 1010 Other raw materials: modified PBT polymer, flexible segment, toughening agent, etc. Experimental procedures Sample preparation Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 are mixed according to the above formula to ensure that the raw materials are evenly distributed, and a suitable process (such as melt extrusion) is used to form bristle filament samples.
[0132] Oxidation index test The samples were subjected to an oxidation index (OIT) test. The samples were exposed to an oxygen environment at 250°C, the time when the samples began to oxidize was recorded, and the oxidation resistance of the materials was determined based on the oxidation index.
[0133] Thermogravimetric analysis (TGA) The thermal stability of each sample was tested using a thermogravimetric analyzer (TGA). In a nitrogen atmosphere, the sample was heated from room temperature to 800°C, its thermal gravimetric curve was recorded, and important parameters such as thermal decomposition temperature and initial decomposition temperature were analyzed.
[0134] Data recording and analysis The oxidation index and thermogravimetric analysis data were analyzed, and the high temperature resistance and oxidation resistance of each sample were calculated and compared with those of Example 1.
[0135] Table 2 It can be seen from the experimental data that the oxidation index and thermal stability of Example 1 are significantly better than those of the comparative example group. This shows that the antioxidant 1010 fully exerts its antioxidant effect in Example 1, significantly extending the service life of the material under high temperature and oxidative environment. Specifically, the antioxidant 1010 can react with free radicals in the polymer to prevent the breakage and degradation of the polymer chain, thereby enhancing the stability of the material under high temperature conditions. In addition, the combination of the toughening agent (EVA nanoparticles) and the flexible chain segment in Example 1 not only improves the flexibility of the material, but also improves the thermal stability of the material. The toughening agent can increase the flexibility of the PBT molecular chain and prevent thermal cracking in a high temperature environment, thereby increasing the decomposition temperature in the thermal weight loss curve.
[0136] Compared with Example 1, the oxidation index and thermal stability of Comparative Examples 1, 2 and 3 are lower, indicating that their antioxidant performance and thermal stability are limited. Comparative Examples 1 and 2 lack the protection of antioxidants, resulting in easy thermal degradation at high temperatures. Although Comparative Example 3 has added flexible segments, due to the lack of the refining effect of nanoparticle toughening agents, its antioxidant performance and thermal stability are poor, resulting in a lower decomposition temperature and a lower oxidation index. Therefore, the synergistic effect of antioxidants, toughening agents and flexible segments is a key factor in improving the high temperature stability and antioxidant properties of materials. Experiment 3: Material flexibility and durability test Purpose This experiment aims to evaluate the flexibility and durability of different examples and comparative examples under repeated bending and stretching conditions, simulating the performance of bristle filaments in actual use. Through repeated bending experiments (bending times and stress tests), the fatigue performance, crack generation and rupture of the material under high stress conditions are tested, and the effect of toughening agents and flexible segments on improving material performance is evaluated.
[0137] Experimental Materials Embodiment 1: Modified PBT polymer (including flexible segments, polyether segments and polyester segments), mass percentage 60% Toughening agent: Ethylene-vinyl acetate (EVA) copolymer nanoparticles, particle size 10-50 nanometers, mass percentage 10% Other additives: antioxidant (such as antioxidant 1010, mass percentage 1%) Mechanical properties test sample size: diameter 0.3mm, length 50mm Comparative Example 1: Modified PBT polymer (without soft segments), mass percentage 70% Toughener: Ethylene-vinyl acetate (EVA) copolymer, particle size 10-50 nanometers, mass percentage 5% Other additives: Antioxidant 1010, mass percentage 1% Mechanical properties test sample size: diameter 0.3mm, length 50mm Comparative Example 2: Modified PBT polymer (including soft segments and polyether segments), mass percentage 65% Toughener: None Other additives: Antioxidant 1010, mass percentage 1% Mechanical properties test sample size: diameter 0.3mm, length 50mm Comparative Example 3: Modified PBT polymer (without soft segments), mass percentage 70% Toughener: Ethylene-vinyl acetate (EVA) copolymer, particle size 50-100 nanometers, mass percentage 10% Other additives: No Mechanical properties test sample size: diameter 0.3mm, length 50mm Experimental procedures Sample preparation The bristle filaments of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 were prepared according to the above formula and process, ensuring that the diameter and length of each group of samples were consistent. The bristle filaments prepared by the melt extrusion process should have no obvious surface defects.
[0138] Flexibility test Use an electronic tensile testing machine to perform bending tests on different samples. During the test, the sample is clamped between two brackets and repeatedly bent to a certain angle (such as ±90°) at room temperature. The number of bends and the bending angle that each sample can withstand are recorded until obvious cracks or breaks appear.
[0139] Test conditions: temperature: 25°C, humidity: 50%; bending angle: ±90°; bending frequency: 10 times per second, for 1000 times.
[0140] Tensile fatigue test A standard tensile testing machine was used to conduct tensile tests on the samples to simulate the tensile conditions in actual use. Each group of samples was stretched on the tensile testing machine, and the tensile strength and elongation were recorded until the sample broke.
[0141] Test conditions: temperature: 25°C, humidity: 50%; stretching speed: 5 mm / min; stretching sample length: 50 mm.
[0142] Data recording and analysis The bending times, tensile strength, elongation and occurrence of cracks / breaks of each sample were recorded to analyze its flexibility and durability. The performance differences between different embodiments and comparative examples were compared based on the test data. Sample No. Bending times Bending Angle Tensile Strength Elongation Rupture duration Embodiment 1 1500 times ±90° 35.8 (MPa) 200% 5.3 (minutes) Comparative Example 1 1200 times ±85° 32.1(MPa) 185% 4.7 (minutes) Comparative Example 2 1000 times ±80° 30.5(MPa) 170% 4.3 (minutes) Comparative Example 3 800 times ±75° 28.4 (MPa) 160% 3.8 (minutes)
[0143] Table 3 It can be seen from the experimental data that the performance of Example 1 in terms of bending times and tensile strength is better than that of the comparative example group, indicating that the addition of the toughening agent (EVA nanoparticles) and flexible segments in the present invention greatly improves the flexibility and durability of the bristle filaments. The toughening agent can increase the flexibility of the PBT segment at the molecular level, alleviate stress concentration during repeated bending and stretching, and reduce the probability of breakage. At the same time, the flexible segments (such as polyether segments and polyester segments) improve the stretchability and deformation capacity of the material, making the bristle filaments less prone to cracks or breaks under repeated bending and stretching conditions. The change mechanism of these materials shows that the combined effect of the toughening agent and the flexible segment improves the overall mechanical properties of the material.
[0144] The samples in the comparative group, although also containing flexible segments and PBT polymers, performed poorly in the repeated bending and stretching tests due to the lack of the effect of the nanoparticle toughening agent. The bending times of comparative examples 1 and 2 were relatively small, and the tensile strength and elongation were low, which made it easy to crack or break. In particular, in comparative example 3, due to the large particle size of the toughening agent EVA nanoparticles (50-100 nanometers), its dispersibility was poor, resulting in the formation of microscopic aggregates in the material, affecting the overall flexibility performance.
[0145] Experiment 4: Antioxidant performance test Purpose This experiment aims to evaluate the antioxidant performance of different embodiments and comparative examples in an oxidative environment. By exposing different samples to an oxidative aging test under a high temperature and high humidity environment, the difference between the antioxidant performance of the present invention and that of conventional technologies is verified, especially the antioxidant capacity after long-term use. The antioxidant effect of the combination of toughening agent and antioxidant is evaluated by analyzing the surface gloss, tensile strength, and antioxidant composition.
[0146] Experimental Materials Embodiment 1: Modified PBT polymer (including flexible segments, polyether segments and polyester segments), mass percentage 60% Toughening agent: Ethylene-vinyl acetate (EVA) copolymer nanoparticles, particle size 10-50 nanometers, mass percentage 10% Other additives: Antioxidant 1010, mass percentage 1% Test sample: diameter 0.3mm, length 50mm Comparative Example 1: Modified PBT polymer (without soft segments), mass percentage 70% Toughener: Ethylene-vinyl acetate (EVA) copolymer, particle size 10-50 nanometers, mass percentage 5% Other additives: Antioxidant 1010, mass percentage 1% Test sample: diameter 0.3mm, length 50mm Comparative Example 2: Modified PBT polymer (including soft segments and polyether segments), mass percentage 65% Toughener: None Other additives: Antioxidant 1010, mass percentage 1% Test sample: diameter 0.3mm, length 50mm Comparative Example 3: Modified PBT polymer (without soft segments), mass percentage 70% Toughener: Ethylene-vinyl acetate (EVA) copolymer, particle size 50-100 nanometers, mass percentage 10% Other additives: No Test sample: diameter 0.3mm, length 50mm Experimental procedures Sample preparation The bristle filaments of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 were prepared according to the above formula and process, ensuring that the diameter and length of each group of samples were consistent and the surface was smooth without obvious defects.
[0147] Oxidative aging test Each group of samples was exposed to a controlled high temperature and high humidity environment for oxidation aging test. The specific conditions were: temperature of 80°C, relative humidity of 90%, and continuous exposure time of 200 hours. During this period, samples were sampled every 50 hours and tested for changes in surface gloss, tensile strength, and antioxidant concentration.
[0148] Surface gloss test The glossiness of the surface of each group of samples was tested using a gloss meter, and the changes in glossiness before and after oxidation were recorded. The higher the glossiness value, the better the antioxidant performance of the sample.
[0149] Test conditions: gloss meter measurement, light source angle 60°, standardized data output.
[0150] Tensile strength test The tensile tester is used to perform tensile tests on samples exposed to an oxidative environment and record the changes in tensile strength. This test is used to evaluate the degree of mechanical degradation of samples after long-term exposure.
[0151] Test conditions: temperature: 25°C, humidity: 50%; stretching speed: 5 mm / min; stretching sample length: 50 mm.
[0152] Antioxidant component analysis The antioxidant components in the samples were analyzed using high performance liquid chromatography (HPLC), and the changes in antioxidant concentrations before and after oxidation were recorded. A lower antioxidant concentration indicates that the sample is more oxidizable.
[0153] Data recording and analysis The surface gloss, tensile strength and antioxidant concentration changes of each sample were recorded, and the antioxidant properties of different materials under high temperature and high humidity environments were analyzed. Sample No. Glossiness changes Changes in tensile strength Changes in antioxidant concentration Embodiment 1 -12% -15.6MPa -6.7% Comparative Example 1 -30% -25.8MPa -15.2% Comparative Example 2 -20% -19.4MPa -10.4% Comparative Example 3 -35% -28.3MPa -18.5%
[0154] Table 4 In this experiment, after 200 hours of treatment in a high temperature and high humidity oxidative environment, the gloss, tensile strength and antioxidant concentration of all samples changed to a certain extent. However, by comparing the data of different embodiments and comparative examples, it can be clearly seen that the performance of the bristle filaments of Example 1 after oxidative aging is better than that of other samples, indicating that the combination of toughening agent and antioxidant in the present invention significantly improves the antioxidant performance of the material.
[0155] From the perspective of mechanism, the synergistic effect of the toughening agent (EVA nanoparticles) and the antioxidant in Example 1 plays a key role. The addition of EVA nanoparticles not only enhances the flexibility of the PBT material, but also enhances the stability of its molecular structure and reduces the oxidation reaction rate in a high temperature and high humidity environment. In addition, the uniform distribution of the antioxidant 1010 helps to eliminate chain breaks caused by oxidation reactions, further improving the aging resistance of the material.
[0156] In contrast, due to the low concentration of antioxidants and improper use of toughening agents, the antioxidant properties of Comparative Examples 1 and 3 were significantly reduced, and the surface glossiness change and tensile strength decay were more significant, indicating that the reasonable combination of toughening agents and antioxidants is the key factor in improving the antioxidant properties of PBT facial brush bristles. Although Comparative Example 2 used a flexible segment, no toughening agent was added, resulting in its antioxidant performance being inferior to that of Example 1.
[0157] In summary, the toughening agent and antioxidant compound system used in Example 1 has significant advantages in improving the antioxidant properties of PBT facial brush bristles, and its improvement mechanism and significant experimental results verify the superiority of the present invention in practical applications.
[0158] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A high-toughness and soft PBT face-washing brush bristle, characterized in that: The bristle filaments are mainly composed of modified PBT polymers, which contain flexible segments, which are polyether segments or polyester segments, and the mass percentage concentration of the modified PBT polymer is 60% to 80%. The bristle filaments further contain a toughening agent, which is ethylene-vinyl acetate copolymer nanoparticles, and the mass percentage of the toughening agent is 5% to 15%.
2. The high-toughness and soft PBT face-washing brush bristle according to claim 1, characterized in that: The mass percentage of the soft segment is 20% to 40%.
3. The high-toughness and soft PBT face-washing brush bristle according to claim 1, characterized in that: The molecular weight of the modified PBT polymer ranges from 40,000 to 60,000 Da.
4. The high-toughness and soft PBT face-washing brush bristle according to claim 1, characterized in that: The anti-oxidation property of the bristle filaments is obtained by compounding 1,4-butanediol and an antioxidant 1010, wherein the mass percentage of the antioxidant 1010 is 1% to 2%.
5. The high-toughness and soft PBT face-washing brush bristle according to claim 1, characterized in that: The toughening agent is ethylene-vinyl acetate copolymer nanoparticles, the size of the EVA nanoparticles is 10 to 50 nanometers, and the particles are uniformly dispersed in the PBT polymer.
6. The high-toughness and soft PBT face-washing brush bristle according to claim 1, characterized in that: The dispersibility of the toughening agent EVA nanoparticles is improved by ultrasonic dispersion technology, ensuring uniform particle size and distribution.
7. A method for preparing high-toughness and soft PBT face-washing brush bristles, according to the high-toughness and soft PBT face-washing brush bristles described in any one of claims 1 to 6, characterized in that: The following steps are involved: Step 1: uniformly mixing the modified PBT polymer with a flexible segment, a toughening agent, a lubricant and an antioxidant, wherein the flexible segment is a polyether or polyester segment, the toughening agent is ethylene-vinyl acetate copolymer nanoparticles, the size of the toughening agent particles is 10 to 50 nanometers, and the particles are uniformly distributed; Step 2: feeding the uniformly mixed mixture into a screw extruder, performing melt extrusion in the extruder, and forming a filamentous product after extrusion; Step 3, cooling the extruded filament product through a cooling water tank to solidify it into shape; Step 4: The cooled filamentous product is pulled by a pulling device, and is dried and pressed, and finally rolled into a roll to obtain a high-toughness and soft PBT facial brush bristle.
8. The method for preparing high-toughness and soft PBT face-washing brush bristles according to claim 7, characterized in that: The mass percentage of the lubricant is 1% to 3%.
9. The method for preparing high-toughness and soft PBT face-washing brush bristles according to claim 7, characterized in that: The size of the toughening agent EVA nanoparticles is 10 to 50 nanometers, and the particles are evenly distributed through ultrasonic dispersion technology to ensure their dispersibility in the PBT polymer.
10. The method for preparing high-toughness and soft PBT face-washing brush bristles according to claim 7, characterized in that: The temperature of the cooling water tank is controlled between 30°C and 50°C.